Vitamin D status in children and adolescents with type 1 diabetes in a specialized diabetes care centre in Bangladesh. Issue 1 (12th November 2021) - Zabeen, Bedowra; Nahar, Jebun; Ahmed, Bulbul; Tayyeb, Samin; Islam, Nasreen; Azad, Kishwar
Abstract: Objectives: High prevalence of vitamin D deficiency (VDD) in children and adolescents with type 1 diabetes (T1D) was found in several epidemiological studies. The current study aimed to assess the Vitamin D status in children and adolescents with T1D and to examine the influence of the disease characteristics on vitamin D status in a specialized care centre in a tertiary hospital in Bangladesh. Methods: Participants were enrolled in the cross‐sectional study at the time of a regularly scheduled visit to the CDiC Paediatric Diabetes Center in BIRDEM 2(Bangladesh Institute of Research and Rehabilitation of Diabetes Endocrine and Metabolic Disorders), a tertiary care hospital in Bangladesh. The demographic and clinical data were collected through medical records with a structured questionnaire. Results: Among sixty study participants, most had inadequate levels of vitamin D: deficiency 31 (51.7%), insufficiency 14 (23.3%) and sufficiency 15 (25.0%). Participants with vitamin D deficiency (VDD) were significantly older compared to the sufficient and insufficient group ( p  = .029), and were residing in urban areas ( p  = .036) and from higher socioeconomic status ( p  = .014). BMI was significantly higher in VDD compared to the sufficient group ( p  = .040). Although we observed higher median values of daily insulin requirements and HbA1c values in patients with VDD compared to patients with vitamin D insufficiency or vitamin D sufficiency, these differences did not reach statistical significance. Conclusions: The present study revealed that the prevalence of vitamin D deficiency and insufficiency among T1 diabetes children was very high. Future studies in large sample are required to assess hypovitaminosis D in youth with T1D and also the possible relating factors of vitamin D deficiency. Abstract : Participants with Vitamin D deficiency (VDD) were significantly older ( p  = .029), were residing in urban areas ( p  = .036) and from higher socioeconomic status ( p  = .014) compared to the sufficient and insufficient group. The present study revealed that the prevalence of vitamin D deficiency and insufficiency among T1 diabetes children was very high in Bangladesh.